CSR and Financial Performance of Renewable Energy Companies - Alif, Kaiser (My University, 2025)
This thesis analyzes how CSR activities affect financial performance in renewable energy companies within the ten-year period of 2014 to 2023. Based on stakeholder theory and the resource-based view, it examines which CSR dimensions has more influence in this relationship. The positive relationship of environmental performance ROA indicates that sustainability initiatives can enhance operational efficiency and profitability. ROE has a positive but statistically insignificant relation with social performance, indicating that stakeholders might provide benefits to shareholders, but may not be predictable. Overall ESG scores do not have a direct effect, indicating that CSR is affecting financial outcomes via different channels than a uniform bundle. These results support both the resource-based view and stakeholder theory by demonstrating that targeted environmental and social strategies can result in business value. The study recommends managers and policymakers to invest in certain CSR activities particularly in the environmental area to ensure both sustainability outcome and financial performance while promoting broader environmental and social objectives.
Keywords: societal responsibility; sustainable development; environmental responsibility; corporate responsibility; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance